Fotoeletrorredução de CO2 empregando óxidos nanoestruturados - Almeida, Juliana de [UNIFESP] (2016)
The performance of the heterogeneous photocatalysis in wastewater treatment for the removal of organic pollutants, as well as for gaseous emissions, is associated to semiconductor photo-activity. TiO2 is a semiconductor commonly employed for photocatalytic processes, due to its corrosion resistance, chemical stability, low toxicity, and photoactivity. It has an energy band gap of 3.2 eV, which is equivalent to an absorption wavelength (?) shorter than 388 nm, which corresponds to UV radiation and becomes a major obstacle for its use under sunlight. In this study, TiO2 nanotubes (NT/TiO2) were modified with Cu nanoparticles, creating a p-n heterostructure in order to increase the photocatalytic activity, by the change of the absorption spectrum to longer wavelengths, the decrease of the rate of recombination of photogenerated charges, and the optimization of its application for photoreduction processes. The NT/TiO2 were synthesized on Ti substrate by anodic process and modified by electrodeposition. Voltammetric studies employing 0.01 mmol L-1 CuSO4 in different electrolytes, 0.1 mol L-1 of Na2SO4 or 0.01 mol L-1 C3H6O3 were performed to investigate the influence of the electrolyte and the potential range to be applied in electrodeposition process. In both electrolytes, the morphology, amount and distribution of Cu nanoparticles on NT/TiO2 showed strong influence of applied potential. High values of cathodic current was obtained in photocurrent experiments using NT/TiO2 modified with Cu at 0,70 and -0,85 V vs. Ag/AgCl, using Na2SO4 e C3H6O3, respectively, These samples were submitted to heat treatment to convert metallic Cu in Cu2O (NT/TiO2-Cu2O) and CuO (NT/CuO-TiO2). The NT/TiO2-Cu2O and NT/CuO-TiO2, synthesized in different electrolytes, were applied in CO2 photoelectroreduction in 0.1 mol L-1 NaHCO3, pH 8.0. Only the NT/TiO2-CuO electrode synthesized in C3H6O3 solution was able to produce acetone, ethanol and methanol. The result shows that the morphology and size of the cupric oxide nanoparticles are fundamental in the electrode efficiency, making it more attractive to contribute as a source for the production of fuels. The efficiency was certificated by its band gap energy which value was 46 % lower than that of undecorated NT/TiO2.